PRIMACY OF LIQUID MEDIUM TECHNIQUE ON PROTOCORM LIKE BODIES PROPAGATION OF Phalaenopsis sp ORCHIDS IN TISSUE CULTURE - Kriswanto, Budi; Soeparjono, Sigit; Restanto, Didik Pudji (BIOVALENTIA: Biological Research Journal, 2020)
Tissue culture have been used for plant propagation generally, and the medium has been important role in its growth. Vegetative propagation on Phalaenopsis sp orchids can be through the protocorm like bodies (PLB). Medium of affect on propagation of PLB was carried out on medium type, kind of basal medium and concentrations ratio of naphtaleneacetic acid (NAA) and benzylamino purine (BAP). The experiment used Completely Randomized Factorial Design with 3 replications and continued with the Duncan Multiple Range Test (DMRT) if there were significant differences. The results showed that the best callus formed in a combination of solid medium type and Murashige & Skoog (MS) basal medium was 100%. The most number of PLB produced from a combination of liquid medium types and a concentration ratio of NAA 1 mgL-1 and BAP 5 mgL-1, the most number of plantlet produced from a combination of MS basal medium and the concentrations ratio of NAA 0.1 mgL-1 and BAP 0.1 mgL-1, the number of PLB germination and PLB with leaves were influenced by each single factor.